Functional Corticomuscular Signal Coupling Is Weakened during Voluntary Motor Action in Cancer-Related Fatigue - Changhao Jiang; Qi Yang; Tingting Chen; Vlodek Siemionow; Vinoth K. Ranganathan; Alice F. Yan; Guang H. Yue (Neural Plasticity)
Background and Purpose. Cancer-related fatigue (CRF) is widely recognized as one of the most common symptoms and side effects of cancer and/or its treatment. However, neuropathological mechanisms contributing to CRF are largely unknown, and the lack of knowledge makes CRF difficult to treat. Recent research has shown dissociation between changes in the brain and muscle signals during voluntary motor performance in cancer survivors with CRF, and this dissociation may be caused by an interruption in functional coupling (FC) of the two signals. The goal of this study was to assess the FC between EEG (cortical signal) and EMG (muscular signal) in individuals with CRF and compare the FC with that of healthy controls during a motor task that led to progressive muscle fatigue. Method. Eight cancer survivors with CRF and nine healthy participants sustained an isometric elbow flexion contraction (at 30% maximal level) until self-perceived exhaustion. The entire duration of the EEG and EMG recordings was divided into the first-half (less-fatigue stage) and second-half (more-fatigue stage) artifact-free epochs without overlapping. The EEG-EMG coupling (measured by coherence of the two signals) in each group and stage was computed. Coherence values at different frequencies were statistically analyzed using a repeated-measure general linear model. Results. The results demonstrated that compared to healthy controls, CRF participants sustained the contraction for a significantly shorter time and exhibited robust and significantly lower EEG-EMG coherence at the alpha (8~14 Hz) and beta (15~35 Hz) frequency bands. Both the CRF and healthy control groups exhibited significantly decreased EEG-EMG coherence from the less-fatigue to more-fatigue stages at the alpha and beta frequency bands, indicating fatigue-induced weakening of functional corticomuscular coupling. Conclusion. Impaired functional coupling between the brain and muscle signals could be a consequence of cancer and/or its treatment, and it may be one of the contributing factors to the abnormal feeling of fatigue that caused the early failure of sustaining a prolonged motor task.